2010
DOI: 10.4314/sajas.v39i4.51136
|View full text |Cite
|
Sign up to set email alerts
|

Feed efficiency and carcass and meat quality characteristics of bulls finished on diets containing varied proportions of wheat straw and wet sugar beet pulp

Abstract: Fifteen young Holstein Friesian bulls (18 mo of age) were divided into three groups of five. All groups were fed a diet consisting of 60% concentrate and 40% roughage. The control (C) group received a mixture of dry meadow hay, dry lucerne and wheat straw as roughage. The second and third treatment groups were fed a similar mixture of roughage partially substituting wheat straw with wet sugar beet pulp (SBP) at levels of 4% and 8% on a dry matter (DM) basis, respectively. Dry matter intake and feed efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
(13 reference statements)
2
3
8
Order By: Relevance
“…A study reported back fat thickness for concentrate with roughage separately (CON) and total mixed ration (TMR) models in Hanwoo steers, 11.95 and 13.95 mm, respectively (Chung et al, 2017). The fat thickness over LD in the study was different from a study of Yüksel et al (2009), who reported that fat thickness over LD did not differ among control, 4% SBP, 8% sugar beet pulp (SBP). On the other hand, the study was similar to Yüksel et al (2019), who indicated that the fat thickness over LD differed among treatment groups.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…A study reported back fat thickness for concentrate with roughage separately (CON) and total mixed ration (TMR) models in Hanwoo steers, 11.95 and 13.95 mm, respectively (Chung et al, 2017). The fat thickness over LD in the study was different from a study of Yüksel et al (2009), who reported that fat thickness over LD did not differ among control, 4% SBP, 8% sugar beet pulp (SBP). On the other hand, the study was similar to Yüksel et al (2019), who indicated that the fat thickness over LD differed among treatment groups.…”
Section: Resultscontrasting
confidence: 70%
“…The studies of Hanwoo Steers at different yield grades revealed no significant effect of live BW at slaughter on carcass leanness and fatness (Jung et al, 2013). However, according to some studies, the findings in this study were found to be low (Yüksel et al, 2009;Shin et al, 2011).…”
Section: Resultscontrasting
confidence: 64%
“…The finding differs from the results reported by Barham et al [15]. They are lower than values reported by Hollao et al [7], and are higher than those reported by Yüksel et al [9] and Yüksel et al [11]. Hot carcass, edible meat, and pelvic fat are interrelated.…”
Section: Discussioncontrasting
confidence: 69%
“…Similar findings were reported by Ozluturk et al [8], who observed significant differences in feed efficiency between age groups. Yüksel et al [9] and Pazdiora et al [10] reported similar results in hot carcass dressing of old bulls, and Yüksel et al [11] and Catrileo et al [12] reported similar results in hot carcass dressing of young bulls, but different from the values determined for Hungarian Grey by Hollo et al [7] and Lopez-Campos [13]. Pelvis fat is a factor that affects the quality grade of the carcass, yield grade score, and fattening cost.…”
Section: Discussionmentioning
confidence: 89%
“…In spite of the importance of cattle in Turkey there has been a paucity of recent publications on the species in the international literature. Those that have been published include papers relating to animal health and disease (Cetinkaya et al, 2003;Aslantas et al, 2006;Temizel et al, 2009), production on state farms (Ekerden and Ozkutuk, 1990), some aspects of the biochemistry of milk (Polat, Gencoglu and Turkmen, 2009;Gurcan, 2011) and reports of small-scale experiments on meat production (Ozluturk et al, 2004;Unlu et al, 2008;Yuksel et al, 2009). The current paper aims to provide information on some of the main cattle populations of Turkey as well as some perceptions of their production and is one of a series (Wilson, Yilmaz and Ertugrul, 2011;Wilson, 2011a, 2011b) that will eventually cover all the nation's domestic animal species.…”
Section: Introductionmentioning
confidence: 99%